The Sonderkommando photographs: a possibility for reconciled commemoration of a sublime historical event - Ramos Mollá, Paula (Estudios de Filosofía, 2022)
In this paper I consider the four images from Auschwitz analyzed by Didi- Huberman in Images in Spite of All —the so-called Sonderkommando photographs— through the lens of the “historical sublime” as proposed by historian Eelco Runia. These photographs are taken as an example of a possible reconciled aesthetic experience with an “unimaginable” past that horrifies us. Moreover, I argue that aesthetic depictions are able to champion a model of historical commemoration which makes these events imaginable again. In order to show this, I will first employ the concept of the “sublime historical event” which Runia proposes to interpret the Holocaust’s historical catastrophe. Runia’s “historical sublime” provides a framework to understand the process of becoming what “we are no longer” through the invention of new identities that defy our former ones and explain historical discontinuities. Secondly, I will examine the Sonderkommando photographs by applying Runia’s notion of commemoration to the viewer’s aesthetic experience of these images. I will finally suggest the possibility of a reconciliation with our former identities, those who committed sublime historical acts with which we no longer identify, thanks to this aestheticized experience of commemoration.